2009
DOI: 10.1017/s0140525x09000053
|View full text |Cite
|
Sign up to set email alerts
|

“Fatal attraction” syndrome: Not a good way to keep your man

Abstract: This target article presents an integrated evolutionary model of the development of attachment and human reproductive strategies. It is argued that sex differences in attachment emerge in middle childhood, have adaptive significance in both children and adults, and are part of sex-specific life history strategies. Early psychosocial stress and insecure attachment act as cues of environmental risk, and tend to switch development towards reproductive strategies favoring current reproduction and higher mating eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 148 publications
(184 reference statements)
1
5
0
Order By: Relevance
“…Recently, Del Giudice (2008) reported that studies of children as old as 6 usually fail to discern sex differences in attachment, whereas nearly all of the available studies of children aged 7-11 presenting separate statistics by sex show remarkable sex-biased distributions of insecure styles (Corby, 2006;Del Giudice, 2008;Finnegan et al, 1996;Granot & Mayseless, 2001;Karavasilis, Doyle, & Markiewicz, 2003;see Kerns, Abraham, Schlegelmilch, & Morgan, 2007, for an exception). These sex differences emerge with both attachment questionnaires and doll-play tasks; however, and again paralleling adult findings (van IJzendoorn & Bakermans-Kranenburg, 1996, 2009), they are not evident when attachment interviews focused on past experiences with parents are used in middle childhood (Ammaniti, van IJzendoorn, Speranza, & Tambelli, 2000). Given the still limited database and the modest sample sizes of some investigations, it is clear that we need more work on sex differences, including meta-analyses, before we can draw strong conclusions about the presence-or absence-of sex differences in attachment in middle childhood.…”
Section: Testing the Model: Extant Evidence And Methodological Issuessupporting
confidence: 66%
See 2 more Smart Citations
“…Recently, Del Giudice (2008) reported that studies of children as old as 6 usually fail to discern sex differences in attachment, whereas nearly all of the available studies of children aged 7-11 presenting separate statistics by sex show remarkable sex-biased distributions of insecure styles (Corby, 2006;Del Giudice, 2008;Finnegan et al, 1996;Granot & Mayseless, 2001;Karavasilis, Doyle, & Markiewicz, 2003;see Kerns, Abraham, Schlegelmilch, & Morgan, 2007, for an exception). These sex differences emerge with both attachment questionnaires and doll-play tasks; however, and again paralleling adult findings (van IJzendoorn & Bakermans-Kranenburg, 1996, 2009), they are not evident when attachment interviews focused on past experiences with parents are used in middle childhood (Ammaniti, van IJzendoorn, Speranza, & Tambelli, 2000). Given the still limited database and the modest sample sizes of some investigations, it is clear that we need more work on sex differences, including meta-analyses, before we can draw strong conclusions about the presence-or absence-of sex differences in attachment in middle childhood.…”
Section: Testing the Model: Extant Evidence And Methodological Issuessupporting
confidence: 66%
“…The possible role of anxiety for girls is, to be honest, less clear, although dependent and closeness‐oriented behaviors may turn out to be advantageous in female group relationships (Del Giudice, 2009b). Some researchers have suggested that anxious attachment in girls may relate to relational and indirect aggression, which would make evolutionary sense in the context of female peer competition; unfortunately, up to now attachment research has concentrated almost exclusively on overt, physical aggression, so this possibility has yet to be tested empirically (see Campbell, 2009; Del Giudice, 2009b).…”
Section: The Juvenile Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, anxious attachment could function for females as a means of keeping oneself in close contact with the kin network (Del Giudice, 2009a ;Goetz, Perilloux & Buss, 2009 ); more speculatively, emphasizing immaturity and dependency might work as an attractiveness display directed at males (Marquez & Rucas, 2008 ). In addition, attachment anxiety may predict increased relational/indirect aggression in the context of female peer competition (Campbell, 2009 ;Del Giudice, 2009b ), but since most attachment-aggression studies have focused on overt physical aggression, this intriguing possibility remains to be explored. Finally, insecure attachment in juvenility predicts the early appearance of fl irting and sexual contacts, even in pre-pubertal children (Sroufe et al, 1993 ); this further underlines the emerging functional coupling of the attachment and sexual systems.…”
Section: Sex Differences In Life History Strategiesmentioning
confidence: 99%
“…In this context, ambivalent attachment may be considered a useful strategy for extracting resource investment from kin and peers (Del Giudice, 2009). Such resource-acquisition behaviors driven by ambivalent attachment are not exclusively prosocial; they may also be coercive (Campbell, 2009;Del Giudice, 2009). Thus children who develop an ambivalent attachment style are more likely to adopt both prosocial and coercive strategies to control resources.…”
Section: Rc Theorymentioning
confidence: 99%